Pemikiran Ruang Siswa Sekolah Menengah Pertama dalam Memecahkan Masalah Ruang Berdasarkan Perbedaan Gaya Kognitif - Putra Nazrani Wila; Juniati Dwi; Khabibah Siti (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
Spatial reasoning is a crucial component in mathematics education, particularly in solving geometry problems that require visualization and mental manipulation of objects in space. This study aims to describe the spatial reasoning of junior high school students based on their cognitive styles, namely field independent (FI) and field dependent (FD). The study employed a qualitative approach with a descriptive method. Data were collected through students’ solutions to geometry tasks involving three-dimensional shapes and in-depth interviews with two selected subjects representing each cognitive style. The findings indicate that the field independent subject demonstrated a comprehensive visual representation of geometric objects, formulated problem-solving steps systematically, and exhibited flexibility in positioning objects from various perspectives. However, their ability to mentally rotate objects and evaluate alternative strategies remained underdeveloped. On the other hand, the field dependent subject showed an initial understanding of object structure and was able to construct general problem-solving strategies but struggled with spatial manipulation, maintaining proportions between parts, and engaging in critical reflection of visual representations and solutions. These findings suggest that cognitive style significantly influences students’ spatial reasoning in solving geometry problems.